Proceedings of the Fifth International ACM Conference on Assistive Technologies 2002
DOI: 10.1145/638249.638260
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal feedback

Abstract: Multimodal interfaces have the potential to enhance a user's overall performance, especially when one perceptual channel, such as vision, is compromised. This research investigated how unimodal, b/modal, and trimodal feedback affected the performance of fully sighted users. Limited research exists that investigates how fully sighted users react to multimodal feedback forms, and to-date even less research is available that has investigated how users with visual impairments respond to multiple forms of feedback.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It also provides a more flexible way for users to better perceive and avoid errors [9]. Research has shown that multimodal feedback positively impacts performance, perceived effort, error correction/avoidance, and error reaction time [10][11][12][13]. For example, Ref.…”
Section: Related Work and Contextualizationmentioning
confidence: 99%
“…It also provides a more flexible way for users to better perceive and avoid errors [9]. Research has shown that multimodal feedback positively impacts performance, perceived effort, error correction/avoidance, and error reaction time [10][11][12][13]. For example, Ref.…”
Section: Related Work and Contextualizationmentioning
confidence: 99%
“…Multimodal feedback in teleoperation involves the use of more than one form of feedback during a teleoperation task. Vitense et al (2002) investigated how unimodal, bimodal, and trimodal feedback affect the complex direct manipulation performance of fully sighted users. Investigations were carried out on auditory feedback, haptic feedback, and visual feedback.…”
Section: Related Workmentioning
confidence: 99%